Achieving patient-centred goals in oncology: A retrospective analysis of a domestic activities of daily living group. (December 2020) - Udovicich, Anthea; Edbrooke, Lara; Brown, Ted; Marston, Celia
Introduction: This retrospective study aimed to investigate the effectiveness of a domestic activities of daily living group on the occupational performance and satisfaction of adult inpatients with cancer. Method: A retrospective analysis was completed with an initial cohort of patients who participated in the group during their acute inpatient oncology admission. As part of their routine care, patients completed the Canadian Occupational Performance Measure before and after their participation in the group. The occupational performance and satisfaction scores of 31 adults (mean age 71.61 years, 19 females) were reported descriptively and within-group changes analysed using one-sample t -test analyses and bootstrapping. Results: Most (71%) of the 31 patients were discharged home following their inpatient stay. Canadian Occupational Performance Measure mean (SD) change scores were 3.44 (3.90) for performance and 2.04 (2.16) for satisfaction following participation in one domestic activities of daily living intervention group session. Statistically significant improvements in patients' Canadian Occupational Performance Measure performance and satisfaction scores were demonstrated in the one-sample t -test ( p < .002) and bootstrapping sampling ( p < .002). Conclusion: Acute oncology inpatients who attended a domestic activities of daily living intervention group reported a positive change in Canadian Occupational Performance Measure occupational performance and satisfaction. This study highlights the potential benefit of a group-based domestic activities of daily living intervention in an acute oncology setting.